2015
DOI: 10.6002/ect.mesot2014.p205
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Pulmonary Infections in Heart Transplant Recipients

Abstract: Objectives: Pulmonary infections are life-threatening complications in heart transplant recipients. Our aim was to evaluate long-term pulmonary infections and the effect of prophylactic antimicrobial strategies on time of occurrence of pulmonary infections in heart transplant recipients. Materials and Methods:Patients who underwent heart transplantation between 2003 and 2013 at Baskent University were reviewed. Demographic information and data about immunosuppression and infectious episodes were collected. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…Immunodeficient, immunosuppressed, or individuals with chronic morbidities that place them at risk for infection may take continuous prophylactic antimicrobials to prevent acquisition of potential pathogenic bacteria or fungi (62,212,291). For example, children with sickle cell disease are often on prophylactic penicillin treatment for the first 5 years of life to prevent invasive bacterial infections, such as that caused by the pneumococcus (53,166).…”
Section: Antibioticsmentioning
confidence: 99%
“…Immunodeficient, immunosuppressed, or individuals with chronic morbidities that place them at risk for infection may take continuous prophylactic antimicrobials to prevent acquisition of potential pathogenic bacteria or fungi (62,212,291). For example, children with sickle cell disease are often on prophylactic penicillin treatment for the first 5 years of life to prevent invasive bacterial infections, such as that caused by the pneumococcus (53,166).…”
Section: Antibioticsmentioning
confidence: 99%
“…The only variable we found to be independently associated with overall survival was 30‐day post‐transplant infection (Table ). Other studies have similarly shown that infection increases post‐transplant morbidity and mortality . Infection may also increase predisposition toward AMR .…”
Section: Discussionmentioning
confidence: 83%
“…Other studies have similarly shown that infection increases post-transplant morbidity and mortality. 27,28 Infection may also increase predisposition toward AMR. 29,30 Interestingly, infection rates were similar across groups, suggesting that the use of TPE did not confer additive infectious risk.…”
Section: Discussionmentioning
confidence: 99%
“…Outstanding short-term outcomes in organ transplantation have been achieved by pharmacologic immunosuppression. Despite these accomplishments, the detrimental effects’ life-long continuous immunosuppression compromise long-term allograft survival ( 1 , 2 ). Immunosuppressive combination therapies are not specific and often toxic, resulting in the deterioration of the patient quality of life and severe side effects, including infections and malignancies ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%